2011
DOI: 10.7547/1010215
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral Pain Syndrome and Its Association with Hip, Ankle, and Foot Function in 16- to 18-Year-Old High School Students

Abstract: This study demonstrated greater navicular drop, navicular drift, and dorsiflexion in high school students with PFPS compared with healthy students and highlights that foot posture is important to consider as a factor where patients with PFPS diverge from healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 33 publications
2
82
0
2
Order By: Relevance
“…Among adolescents, the population prevalence is 6-7 % [1,8]. No population-based studies have been conducted among adults, leaving the exact incidence and prevalence unknown in adults.…”
Section: Introductionmentioning
confidence: 95%
“…Among adolescents, the population prevalence is 6-7 % [1,8]. No population-based studies have been conducted among adults, leaving the exact incidence and prevalence unknown in adults.…”
Section: Introductionmentioning
confidence: 95%
“…Although it is common clinical practice to assess and treat the foot and ankle in patients with other lower quarter impairments, very few studies aside from those mentioned previously have looked specifically at the influence that the ankle or foot can have on outcomes related to the hip, pelvis, or lumbar spine. Molgaard et al 48 studied high school students with patellofemoral pain (PFPS) found greater navicular drop, navicular drift, and dorsiflexion in the subjects with PFPS compared with healthy students (Table 2).…”
Section: Clinical Studies Lower Quartermentioning
confidence: 99%
“…The prevalence of PFP at adolescence is about 7% in the general population, 10 and, although there is no conclusive evidence available, it has been suggested that PFP…”
Section: Characteristics and Outcome Of Patellofemoral Pain In Adolesmentioning
confidence: 99%